Wheat polar lipids: sources of variation among near-isogenic wheat lines with different endosperm hardness - Finnie, Sean McIlwain (Kansas State University, 2009)
Starch granule surface components were studied as a function of puroindoline haplotype, starch isolation method, and processing fraction. Commonly grown cultivars and near-isogenic wheat lines that varied in their wheat endosperm hardness were collected. Wheat whole-meal, flour and starch were evaluated for their polar lipid composition. Water-washed starch was isolated using a modified batter method and a dough method. Direct infusion tandem mass spectrometry was used to identify the lipid species in the extracts. A total of 155 polar lipid species in wheat meal, flour and starch were quantitatively characterized. The predominant polar lipid classes were digalactosyldiglycerides, monogalactosyldiglycerides, phosphatidylcholine, and lysophosphatidylcholine. Wheat whole-meal, flour and surface-starch contained greater concentrations of total galactolipids while internal-starch lipids contained greater concentrations of monoacyl phospholipids. Wide ranges in starch surface polar lipid concentrations were observed between the two starch isolation methods. Starch isolation methods provided a greater source of variation than did wheat kernel hardness. When dough is optimally mixed the lipids originally on the surface of wheat starch become incorporated into the gluten phase of the dough, whereas in a batter system the starch-surface lipids stay associated with the starch granule surface. The greatest quantities of polar lipids on the starch surface occurred when both puroindoline proteins were present on starch in their wild-type form. Starch surface polar lipid content decreased dramatically when one of the puroindoline proteins was null, or if the puroindoline-b (pin-b) was in the mutated form (Tryptophan-44 to Arginine). Within the hard textured samples, more polar lipids were present on the starch surface when pin-b was in its wild-type form and puroindoline-a (pin-a) was null than when pin-a was in its wild-type form and pin-b was null. The lowest amount of polar lipids were present when pin-b was mutated (Tryptophan-44 to Arginine) and pin-a was in its wild-type form. This indicates the relative importance of pin-b’s presence and structure as it relates to lipid association with the starch granule surface.
Keywords: Wheat; Polar; Lipid; Starch; Surface; Puroindoline; Agriculture, Food Science and Technology (0359)